The imperial cruise [large type] : a secret history of empire and war - Bradley, James, 1954- (Little Brown & Co., 2009)
Analyzes the multinational conflicts that set the stage for World War II, the Chinese communist revolution, and the Korean War, documenting Theodore Roosevelt's 1905 diplomatic mission in the Pacific through which the United States forged ill-fated covert agreements.